DISTRIBUTION OF ABO AND RHESUS BLOOD GROUPS IN GENERAL POPULATION OF DISTRICT DIR UPPER - Shah, Hussain; Haram, Uzma; Naz, Farhat; Haseeb, Abdul; Ullah, Rooh; Jan, Arif; Shah, Saliman (Pakistan Journal of Physiology, 2016)
Background: The ABO and Rhesus blood groups are of utmost clinical importance. This study was conducted to determine the distribution of ABO and Rhesus blood groups in general population of District Dir Upper, Khyber Pakhtunkhwa, Pakistan during the year 2014. Methods: Data were collected from blood banks and laboratories in the district, entered into SPSS and analysed through percentage method and χ2 test at 95% confience level. Allelic frequencies were calculated by Hardy-Weinberg equation. Results: Record of a total of 1,000 subjects (481 males and 519 females) was included in the study. The highest percentage was recorded for blood group A (32.1%), followed by blood group B (29.8%) and O (25.7%) while the lowest prevalent group was AB (12.4%). Overall, 86.4% of subjects were Rh-positive. In males, distribution of blood groups A, B, O and AB was 16.6%, 15.4%, 9.8%, and 6.3% respectively. In females the distribution was 15.5%, 14.4%, 15.9%, and 6.1% for blood groups A, B, O and AB respectively. The distribution of Rh-positive phenotype was 40.7% in males and 46.0% in females. Allelic frequencies observed for A, B and O were 0.253, 0.240, and 0.507 respectively while for D and d were 0.631 and 0.368 respectively. Conclusion: The principal blood group in district Dir Upper is A, and majority of people are Rh-positive. Keywords: , , , , Pak J Physiol 2016;12(4):37–9